Evolution of Rosemont’s indeterminate for chronic pancreatitis in recurrent acute pancreatitis patients with 1-year follow-up: A prospective case series - Vaidya, Arun; Partha Sarathi Patra (Asian Journal of Medical Sciences, 2023)
Some patients presenting with recurrent acute pancreatitis (RAP), while undergoing endoscopic ultrasound (EUS), are classified as indeterminate for chronic pancreatitis (CP) according to Rosemont criteria. We are describing the clinical and radiological evolution of 14 such patients for 1 year. All the patients were closely followed up at 3 monthly intervals and subjected to ultrasound abdomen and blood sugar profile 6 monthly and EUS after 12 months. Males were 93%. Median age was 26 years. Most common etiology of RAP was idiopathic followed by ethanol and hypertriglyceridemia. On 1-year follow-up, 35.7% remained pain free and 28.6% had acute pancreatitis attack. Endocrine and exocrine insufficiency seen in one and two patients, respectively. Follow-up EUS in eight patients revealed Rosemont “normal” in 1, “Indeterminate” in 2, suggestive of CP in 3, and consistent with CP in two patients. Therefore, Rosemont’s “Indeterminate’’ progress to suggestive/consistent with CP in majority of patients.